1989
DOI: 10.1021/bi00429a017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cDNA encoding human nucleophosmin and studies of its role in normal and abnormal growth

Abstract: A cDNA encoding human nucleophosmin (protein B23) was obtained by screening a human placental cDNA library in lambda gtll first with monoclonal antibody to rat nucleophosmin and then with confirmed partial cDNA of human nucleophosmin as probes. The cDNA had 1311 bp with a coding sequence encoding a protein of 294 amino acids. The identity of the cDNA was confirmed by the presence of encoded amino acid sequences identical with those determined by sequencing pure rat nucleophosmin (a total of 138 amino acids). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
169
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(172 citation statements)
references
References 46 publications
3
169
0
Order By: Relevance
“…Nucleophosmin is found to be more abundant in tumor and growing cells than that in normal resting cells (Feuerstein et al, 1988;Chan et al, 1989). In fact, NPM has been proposed as a tumor marker for prostate (Subong et al, 1999), colon (Nozawa et al, 1996), ovarian (Shields et al, 1997), gastric (Tanaka et al, 1992) and bladder (Yeh et al, 2006) cancers because NPM expression is markedly higher in these tumor cells than that in the corresponding normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleophosmin is found to be more abundant in tumor and growing cells than that in normal resting cells (Feuerstein et al, 1988;Chan et al, 1989). In fact, NPM has been proposed as a tumor marker for prostate (Subong et al, 1999), colon (Nozawa et al, 1996), ovarian (Shields et al, 1997), gastric (Tanaka et al, 1992) and bladder (Yeh et al, 2006) cancers because NPM expression is markedly higher in these tumor cells than that in the corresponding normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group characterized a novel t(11;17)(q13;q21) variant APL translocation (Wells et al, 1996(Wells et al, , 1997 which resulted in the fusion of RARa to the nuclear mitotic apparatus gene, NuMA (Lydersen and Pettijohn, 1980;Sparks et al, 1993). A variant t(5;17)(q35;q21) APL translocation, which fuses RARa to the nucleophosmin gene (NPM) (Kang et al, 1974;Chan et al, 1989) has also been recently identiÂźed (Redner et al, 1996). Like PML-RARa and PLZF-RARa chimeric proteins, it appears that NPM-RARa shares the ability to act as a ligand-dependent transcriptional activator of retinoic acid responsive genes, in vitro (Redner et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, however, analyses of the abnormal proteins derived from chromosomal translocations have provided crucial insights into the molecular mechanisms of tumorigenesis in a variety of leukemias and lymphomas (Rabbitts, 1994;Look, 1997). It has been reported that the t(3;5)(q25.1;q34) chromosomal translocation is restricted to MDS and AML except for acute promyelocytic leukemia (Raimondi et al, 1989), and this suggests that the resultant fusion protein (NPM-MLF1) consisting of nucleophosmin (NPM) (SchmidtZachmann and Franke, 1988;Chan et al, 1989) and a novel cytoplasmic protein, myelodysplasia/myeloid leukemia factor 1 (MLF1) (Yoneda-Kato et al, 1996), is involved in dysregulation of pluripotent progenitor cells and plays a role in ine ective hematopoiesis and/or multi-step transformation into overt leukemia.…”
Section: Introductionmentioning
confidence: 99%